Calcium niobate based piezo-resistive materials for high temperature sensor application. Issue 16 (November 2018) - Sivagnanapalani, P.; Sahoo, B.; Panda, P.K.
Abstract: A2 B2 O7 (A= Ca 2+, Sr 2+, B = Nb 5+ ) based perovskite layered structure (PLS) materials are well known for high piezo-resistive properties. These materials display linear behaviour of electric resistance over wide range of temperature ranging from room temperature (RT) to 1000 °C or more, therefore, are promising candidates for high temperature sensor applications. In the present study, the following compositions were prepared by solid state reaction method: (i) pure calcium niobate (CNO) (Ca2 Nb2 O7 ), (ii) CNO + 0.03 mol% of tungsten trioxide (WO3 ), (iii) CNO + 0.03 mol% of cerium dioxide (CeO2 ) and (iv) CNO + 0.03 mol% of neodymium (III) oxide (Nd2 O3 ). The synthesized powders were calcined at 1250 °C for 2 h and were sintered in the temperatures range of 1350–1450 °C. The weight loss observed on samples sintered beyond 1350 °C is due to loss of both CaO and Nb2 O5 formed on decomposition of CNO at high temperature. The samples were characterized for phase analysis by x-ray diffraction (XRD), micro-structural investigation by scanning electron microscope (SEM) and electrical resistivity (ρ). The electrical resistivity found decreased linearly from 10 14 Ω.cm at RT to 10 7 Ω.cm at 900 °C for all the samples. This indicates that pure and doped calcium niobate materials are very good candidates for high temperature sensor applications. Piezoresistive property of these samples was established by measuring the change in electrical resistance with application of static compressive force and was found nonlinear. The addition of dopants has increased the resistivity and ferroelectric properties whereas decreased the piezo-resistive properties.